Two HEmostasis Methods After TransradIal Catheterization: THEMATIC - protocol for a randomized clinical trial - Santos, Simone Marques dos; da Silva, Eneida Rejane Rabelo; Aliti, Graziella Badin; Romero, Paola Severo; Corrêa, Camille Lacerda; Valle, Felipe Homem; Gonçalves, Sandro Cadaval; Wainstein, Marco Vugman; Wainstein, Rodrigo Vugman (Revista Gaúcha de Enfermagem, 2018)
Objective: Randomized clinical trial protocol to evaluate the incidence of radial artery occlusion with two different arterial compression devices after transradial procedures. Methods: Barbeau’s test will be performed in adults scheduled to undergo transradial interventional procedures. Those with A, B, or C plethysmographic patterns will be selected. At the end of the procedure, patients will be randomly assigned (1:1) to receive patent haemostasis with TR Band™ device or conventional haemostasis with an elastic adhesive bandage. The primary outcome is the incidence of radial artery occlusion. Secondary outcomes are Barbeau’s test curve change, additional time to achieve haemostasis, incidence of bleeding at the puncture site, pain severity, development of arteriovenous fistula, radial pseudo aneurysm, any access-site complication requiring vascular surgery intervention and costs between the two devices. Discussion: The results of this trial should provide valuable additional information on the best approach for haemostasis after transradial percutaneous cardiovascular interventions. Keywords: Randomized controlled trial. Cardiac catheterization/adverse effects. Radial artery. Hemostatic techniques.